Community Policing and Crime Control in Riverine Areas: A Study of EPE L.G.A. of Lagos State - Shittu, Olusoga Tasiru (African Journal of Stability and Development (AJSD), 2018)
Community policing is a proactive approach to policing as against traditional policing approach which is reactive in nature. This study examines the role of community policing in crime control in Epe Local Government Area of Lagos State. It employed a mixed method of data collection using questionnaire and in-depth interview (IDI) as its research instrument due to the collaborative nature of the study. The quantitative data elicited through questionnaire were analysed using Statistical Packages for Social Sciences version 23 to generate frequency tables, percentages, chi-square goodness-of-fit to test the statistical significance of responses provided by the respondents, while the qualitative data generated with the aid of in-depth interviews were transcribed, organised, cleaned and analysed to complement the quantitative data. The study’s findings showed that police-public partnership though has helped the police in controlling crime to some extent but more still needs to be done as some community members are still critical of the police. Additionally, implementation of community policing in Epe is still being bedevilled with some challenges such as inadequate training, negative police perceptions, lack of modern crime gadgets, bribery and corrupt practices, inadequate marine policemen among others. The study recommends that members of the public should be more sensitised on the need to partner with the police; and, that there is need to recruit more policemen and train them in accordance with international best practices.